In Silico Study of Inhibition of Activation Of 1A52 Ethanol Extract Leunca Fruit (Solanum nigrum L) - Fajar, In Rahmi Fatria; Anwar, Effionora; Mumpuni, Esti; Agustini, Kurnia; Desmiaty, Yesi (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2024)
The development of science has found a way to prevent skin aging in menopausal women. One of the therapies is estrogen replacement therapy (17β estradiol). Skin aging in menopausal women is associated with decreased ERα expression. Leunca fruit (Solanum nigrum L) is known to contain phytoestrogens and has the potential as an antiaging agent. The purpose of this study was to predict the anti-aging effect of Solanum nigrum ethanol extract compounds through the Erα 1A52 [A] activation pathway. The research method of active substance analysis metabolite profiling was carried out by analyzing physicochemical properties using pkCSM. This analysis was carried out as an initial selection of compound safety for therapy. Molecular docking with the MVD (Free trial) application. The RMSD value ≤ 2Å indicates a valid docking and the application can be used. The results of the in silico study showed that the results of metabolite profiling showed that diosgenin was an agonist against ERα. The compound has physicochemical properties according to the Lipinski standard so that it can bind to ERα. The conclusion is that diosgenin has the potential and can act as a 1A52 [A] inhibitor so it can be used as an antiaging agent.